2000
DOI: 10.1063/1.373045
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions of MnO to 137 GPa

Abstract: An in situ x-ray study up to 137 GPa using a diamond anvil cell combined with synchrotron x-ray radiation has revealed three new phase transitions in MnO. The rhombohedral distortion from a B1 structure starts at about 30 GPa. The volume compression curve of the distorted phase is in good agreement with recent shock compression experiments, suggesting the possibility of a paramagnetic–antiferromagnetic transition associated with the increase of the Néel temperature (TN). A drastic change in the x-ray pattern w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 19 publications
4
34
2
Order By: Relevance
“…The remnant of distorted-B 1 phase, on the other hand, was observed well above 90 GPa to about 120-130 GPa. In contrast, the previous diffraction study suggested an "intermediate" phase in the pressure region between 90 and 120 GPa, without the characterization of crystal structure [7]. These pressure-induced structural/spectral changes of MnO observed in the present study, therefore, provide a coherent picture, suggesting the phase transitions from paramagnetic B 1 to antiferromagnetic dist-B 1 at 30 GPa, to paramagentic B 8 at 90 GPa, and to diamagnetic B 8 at 110 GPa.…”
Section: A the Mott Insulator-metal Transition Of Mno At 110 Gpacontrasting
confidence: 54%
“…The remnant of distorted-B 1 phase, on the other hand, was observed well above 90 GPa to about 120-130 GPa. In contrast, the previous diffraction study suggested an "intermediate" phase in the pressure region between 90 and 120 GPa, without the characterization of crystal structure [7]. These pressure-induced structural/spectral changes of MnO observed in the present study, therefore, provide a coherent picture, suggesting the phase transitions from paramagnetic B 1 to antiferromagnetic dist-B 1 at 30 GPa, to paramagentic B 8 at 90 GPa, and to diamagnetic B 8 at 110 GPa.…”
Section: A the Mott Insulator-metal Transition Of Mno At 110 Gpacontrasting
confidence: 54%
“…Its diffraction pattern at 79 GPa and room temperature quenched from 2000 K turned to be the mixed peaks of CoO (this seems to be rhombohedrally distorted from B1 as Guo et al, 2002, reports) + SiO 2 (CaCl 2 -type). The variation of the diffraction peaks of CoO with increasing pressure at room temperature suggests that CoO has a B1 structure at high pressure and high temperature like FeO and MnO (Kondo et al, 2000(Kondo et al, , 2004. These results indicate that the stable form of CoSiO 3 is CoO …”
Section: Cosiomentioning
confidence: 49%
“…The displacive phase transition has also been observed in FeO (5), MnO (24), and CoO (23) under high pressures. MnO and CoO displayed multiple phase transitions under high pressures (23,24). Nevertheless, the distorted B1 phases transform to the B1 structure upon laser heating, and the B1 structure transforms back to the distorted phases after temperature quench (Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%